Auricular hematoma. Case report. - Zurita-Orrego, Hernán Arturo (2023)
Introduction: Auricular hematoma is the accumulation of blood in the pinna due to the detachment of the perichondrium from the underlying auricular chondral plane, following blunt trauma from direct blows. In this particular case, the size of the hematoma is significant and provides important considerations in similar cases in the future as a source of consultation. Objective: Describe the clinical case of a patient who presented an auricular hematoma, as well as the importance of timely diagnosis and management. Case Presentation: This is a 93-year-old male patient who presented with blunt trauma to the left auricular region that resulted in a major injury, which was managed clinically and surgically, with a favorable outcome. Discussion: The auricular hematoma occurs after a direct trauma to the ear, almost exclusively on the anterior face of the auricle. Typically, once the otohematoma is drained and compression measures are applied, the prognosis is favorable. Recent studies suggest new techniques for its management and for preventing recurrences. Conclusions: Auricular hematoma is a common entity in otorhinolaryngology, which requires timely diagnosis and adequate management, both clinical and surgical, to prevent future sequelae.